PERBANDINGAN ALGORITMA DJIKSTRA DAN WARSHALL DALAM PENENTUAN LINTASAN TERPENDEK KE KOTA KLATEN - Niken Retnowati; Rizka Safitri Lutfiyani (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
Search for the shortest path is a problem that is faced when we want to travel or go somewhere. Klaten City is one of the cities in Central Java. Cities around Klaten include Boyolali. When we go to Klaten city there are several alternative roads or trails that can be chosen from Boyolali. Mathematically this condition can be applied in graphical form to find the shortest path to the city of Klaten. Determination of the shortest path can be found using the Djikstra Algorithm and the Warshall Algorithm. Researchers tried to compare the two methods to get the most optimal result. From the study concluded that the Djikstra algorithm is more effective than the Warshall algorithm for the shortest path from Boyolali to Klaten.